Kevin Lynch in Los Angeles: Reflections on Planning, Politics, and Participation. Issue 3 (2nd October 2018) - Drake Reitan, Meredith; Banerjee, Tridib
Abstract : Problem, research strategy, and findings: Here we examine the legacy of Kevin Lynch in Los Angeles (CA). We begin by describing his contributions to planning at the city and regional scales. We then focus on Los Angeles's central core because of its prominence as a case study in The Image of the City. Specifically, we ask how Lynch's ideas influenced planning efforts for Los Angeles's downtown. We use a mixed-methods approach comprising expert interviews and analysis of archival documents, news stories, oral histories, plans, and reports. Although it is impossible to attribute the evolving physical form of Los Angeles to Lynch, we can see the effects of his thinking in the empowerment of local citizens and in the sensibility of planners and urban designers. Lynch's contribution occurred at both the city and district scales, first as a consultant for the general plan and the visual studies that led to its creation, and second by inspiring the work of planners tasked with remaking Los Angeles's downtown. Takeaway for practice: A principal aim of Lynch's work was for planners to engage with citizens and to understand how the public experiences the city. Planners and urban designers in Los Angeles were inspired by his ideas and were able to use at least some of his vision to navigate the thicket of the planning process.